Conductive hydrogel substrate preparation method and flexible strain sensor
By gentle modification of chitosan and the use of multi-arm alkenyl betaine type crosslinking agent to construct a conductive hydrogel network, the problem of insufficient performance of existing conductive hydrogels is solved, and the high mechanical properties and electrical conductivity are improved, which is suitable for the application of flexible strain sensors.
Patent Information
- Application Number
- CN202411668539.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-03-11
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The low adhesion, poor conductivity and mechanical properties of existing conductive hydrogels limit their application in the field of flexible strain sensors.
By gentle modification on chitosan, it can be better dispersed in the aqueous environment, and a conductive hydrogel network is constructed using a multi-arm alkenyl betaine type crosslinking agent to form a dense three-dimensional crosslinking network structure to improve its mechanical properties and conductivity.
The high mechanical properties and excellent conductivity of the conductive hydrogel are achieved, which enhances its adhesion to human tissues and ensures stable signal detection and seamless connection of the flexible strain sensor.
Smart Images

Figure BDA0005145200160000051 
Figure BDA0005145200160000052 
Figure BDA0005145200160000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of hydrogels, in particular to a method for preparing a conductive hydrogel matrix and a flexible strain sensor. Background Art
[0002] In recent years, the application of flexible wearable devices has become more and more common. For example, multifunctional flexible sensors have been widely used in health care, tissue engineering, soft robotics and other fields. Hydrogel is a three-dimensional network structure polymer soft material. By adding conductive polymers, ionic salts and conductive nanomaterials to the system, the hydrogel can be given a certain conductivity. It can be further assembled into a sensor, which can be used to monitor the responsiveness to changes in the external environment. It has a very broad application prospect in the field of flexible electronic devices such as wearable devices, artificial skin, human-computer interaction systems and soft robots. However, traditional conductive hydrogels have poor mechanical properties and poor conductivity, which limits their further application. Therefore, the preparation of a conductive hydrogel matrix with excellent comprehensive performance has become a hot topic of current research.
[0003] In the process of human activity monitoring, if the contact between the sensor device and the skin is poor, a lot of noise will be generated. In order to ensure the accuracy and reliability of the output signal, it is crucial that the flexible sensor device fits perfectly with the human tissue. Most hydrogel matrices in the prior art have poor adhesion to the tissue. In order to achieve seamless connection between the sensor device and the human body, the prior art mainly uses tape for adhesion. However, this operation will increase the complexity of the device assembly process. In addition, during movement, the flexible sensor device is prone to local poor contact with the human tissue, which will affect the accuracy and sensitivity of the detection results.
[0004] As an important component of flexible electronic devices such as wearable devices, flexible sensors need to have adaptive strain performance, self-adhesion and self-healing properties in practical applications to ensure stable signal detection under repeated deformation; current hydrogel flexible sensor devices still have problems such as low transparency, single sensing function performance and the need for large monitoring instruments for wired monitoring.
[0005] Chitosan is a product of the natural polysaccharide chitin with some acetyl groups removed. It has biocompatibility, degradability and antibacterial properties. Chitosan has been studied in the field of flexible hydrogels. However, the above work is to disperse chitosan in water to enhance the network. The dissolution of chitosan needs to be carried out in an acidic environment, which has certain limitations. The present invention aims to modify chitosan to be water-based in a mild and simple manner so that it can be better dispersed in a water environment system. By preparing a betaine-type cross-linking agent with strong conductive properties for constructing conductive hydrogels and using them as sensors, the application of conductive hydrogels in different fields is further broadened. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a conductive hydrogel matrix and a flexible strain sensor, which solves the problems of low adhesion, poor conductivity and mechanical properties of the existing conductive hydrogels, so as to meet the actual needs of flexible strain sensors for accurately monitoring various human body movements.
[0007] To achieve the above object, the technical solution adopted by the present invention is:
[0008] A method for preparing a conductive hydrogel matrix comprises the following steps:
[0009] Step (1), under a nitrogen atmosphere, add succinic anhydride and acetone to a reaction flask, stir evenly, add polyethylene glycol monomethyl ether, stir at 20-35° C. for 16-32 h, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and chitosan, continue stirring for 12-24 h, and obtain polyethylene glycol monomethyl ether modified chitosan after dialysis and drying.
[0010] Step (2), under nitrogen atmosphere, acrylamide, acrylic acid, organic dispersant, polyethylene glycol monomethyl ether modified chitosan and a structural formula The multi-arm alkenyl betaine type cross-linking agent is stirred evenly at room temperature, and then added to a trisodium citrate aqueous solution with a mass concentration of 0.1-0.2 g / mL. After mixing evenly, it is degassed with nitrogen for 15-30 minutes, ammonium persulfate is added, and stirring is continued for 20-40 minutes. The mixture is transferred to a mold, polymerized at 60-80°C for 3-8 hours, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0011] Furthermore, in step (1), the ratio of succinic anhydride, polyethylene glycol monomethyl ether, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide, and chitosan is (6-10) g:100 g:(8-12) g:(5-9) g:(15-25) g.
[0012] Furthermore, in step (2), the organic dispersant is potassium chloride and glycerol mixed in a mass ratio of 1:1.
[0013] Furthermore, in step (2), the ratio of acrylamide, acrylic acid, organic dispersant, polyethylene glycol monomethyl ether modified chitosan, multi-arm alkenyl betaine type cross-linking agent, and ammonium persulfate is 100g:(5-10)g:(1.5-3)g:(0.5-0.9)g:(0.05-0.25)g:(0.03-0.06)g.
[0014] Furthermore, the preparation method of the multi-arm alkenyl betaine type cross-linking agent in step (2) comprises the following steps:
[0015] Step S1, under a nitrogen atmosphere, add triallylamine and ethanol to a reaction flask, stir evenly, then add 1,3-dibromo-2-propanol and triethylamine, stir to react, after the reaction is completed, concentrate under reduced pressure, and dry to obtain hexaallyl quaternary ammonium salt propanol.
[0016] Step S2, under a nitrogen atmosphere, add hexaallyl quaternary ammonium salt propanol and dichloromethane to a reaction flask, stir evenly, add sodium benzoic acid-3,5-disulfonate, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react at 20-35° C. for 8-16 hours, concentrate under reduced pressure, separate by column chromatography, and dry to obtain a multi-arm alkenyl betaine type cross-linking agent.
[0017] Furthermore, in step S1, the ratio of triallylamine, 1,3-dibromo-2-propanol, and triethylamine is 100 g:(35-50) g:(75-85) g.
[0018] Furthermore, in step S1, the reaction temperature is 60-80° C., and the reaction time is 24-48 h.
[0019] Furthermore, in step S2, the ratio of hexaallyl quaternary ammonium salt propanol, sodium benzoic acid-3,5-disulfonate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 100 g: (90-105) g: (30-45) g: (15-30) g.
[0020] Furthermore, the preparation method described in any one of claims 1 to 8 obtains a flexible strain sensor composed of electrodes installed on a conductive hydrogel matrix.
[0021] Furthermore, flexible strain sensors are used in the preparation of electronic skin, smart clothing, flexible intelligent robots, foldable displays, and tensile strain detection equipment.
[0022] By adopting the above technical solution, the beneficial effects of the present invention are:
[0023] The invention firstly reacts triallylamine with 1,3-dibromo-2-propanol under the action of triethylamine to obtain hexaallyl quaternary ammonium salt propanol, then undergoes an esterification reaction with sodium benzoic acid-3,5-disulfonate to obtain a multi-arm alkenyl betaine type crosslinking agent, then selects simple succinic anhydride and polyethylene glycol monomethyl ether to react and use them to modify chitosan to prepare polyethylene glycol monomethyl ether modified chitosan, and finally polymerizes with acrylamide, acrylic acid, etc. to obtain a conductive hydrogel matrix, which can be used to prepare a flexible strain sensor.
[0024] The multi-arm alkenyl betaine crosslinker contains six alkenyl structures and can be polymerized with acrylamide and the like to form a dense three-dimensional crosslinked network structure. When stretched by external force, greater energy is required to make the molecular segments move. At the same time, chitosan has good water dispersibility after being modified with polyethylene glycol monomethyl ether, and forms physical crosslinks with the hydrogel network through strong hydrogen bonds. At the same time, the physical entanglement of the internal network of the organic hydrogel itself and the strong hydrogen bonds of chitosan synergistically form strong physical crosslinking interactions, and by combining with the original chemical crosslinks, a tightly structured organic hydrogel is formed together, giving it excellent mechanical properties. The tight network structure is conducive to avoiding stress concentration and crack diffusion, and plays a vital role in the toughening of the conductive hydrogel matrix.
[0025] Since the hydrogel uses glycerol salt solution, low concentration potassium chloride solution and non-toxic glycerol to the human body, the organic hydrogel can ensure good biocompatibility on the surface of human skin. Glycerol and even acrylamide, acrylic acid, etc. contain strong hydrogen bonding effects, which can also ensure that the conductive hydrogel matrix has good adhesion on the skin surface.
[0026] The multi-arm alkenyl betaine type cross-linker contains quaternary ammonium salt and sodium sulfonate zwitterions, the dipole-dipole interaction of which is conducive to ion migration and can release the maximum concentration of freely moving ions. At the same time, the modified chitosan is evenly dispersed in the matrix, and the network structure formed provides a better conductive channel for ion migration, further improving the ion migration rate and conductivity, thereby ensuring that the hydrogel has excellent conductivity and is conducive to sensitive signal transmission; the conductive hydrogel matrix can be tightly bonded to substrates such as rubber and tinplate, with high bonding strength, overcoming the problem of poor adhesion between the existing hydrogel matrix and tissue, so that the flexible strain sensor is seamlessly connected to the human body. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0028] Organic dispersant: Potassium chloride and glycerin are uniformly mixed in a mass ratio of 1:1.
[0029] Example 1
[0030] (1) Under nitrogen atmosphere, add 45 g triallylamine and 540 mL ethanol to a reaction flask, stir evenly, then add 20.7 g 1,3-dibromo-2-propanol and 35.1 g triethylamine, react at 70 ° C for 32 h, concentrate under reduced pressure, and dry to obtain hexaallyl quaternary ammonium salt propanol. The preparation reaction formula is as follows:
[0031]
[0032] (2) Under nitrogen atmosphere, 40 g of hexaallyl quaternary ammonium salt propanol and 720 mL of dichloromethane were added to the reaction flask, and after stirring evenly, 40.8 g of sodium benzoate-3,5-disulfonate, 14.4 g of dicyclohexylcarbodiimide and 10 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 25° C. for 12 h, concentrated under reduced pressure, separated by column chromatography, and dried to obtain a multi-arm alkenyl betaine type cross-linking agent. The preparation reaction formula is as follows:
[0033]
[0034] (3) Under nitrogen atmosphere, 2.4 g of succinic anhydride and 660 mL of acetone were added to the reaction flask. After stirring evenly, 30 g of polyethylene glycol monomethyl ether was added and stirred at 30° C. for 24 h. 3.3 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 2.1 g of N-hydroxysuccinimide and 6 g of chitosan were added and stirred for 16 h. After dialysis and drying, polyethylene glycol monomethyl ether-modified chitosan was obtained.
[0035] (4) Under a nitrogen atmosphere, 100 g acrylamide, 8 g acrylic acid, 2.5 g organic dispersant, 0.8 g polyethylene glycol monomethyl ether modified chitosan and 0.05 g multi-arm ene betaine type crosslinker were stirred uniformly at room temperature, then added into a 0.15 g / mL sodium citrate trisodium aqueous solution, mixed uniformly, degassed with nitrogen for 25 min, added with 0.05 g ammonium persulfate, stirred for 30 min, transferred to a mold, polymerized at 70 ° C for 5 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0036] Example 2
[0037] (1) Under nitrogen atmosphere, 30 g of triallylamine and 300 mL of ethanol were added to a reaction flask. After stirring, 10.5 g of 1,3-dibromo-2-propanol and 22.5 g of triethylamine were added. The mixture was reacted at 80 °C for 24 h, concentrated under reduced pressure, and dried to obtain hexaallyl quaternary ammonium salt propanol.
[0038] (2) Under nitrogen atmosphere, 25 g of hexaallyl quaternary ammonium salt propanol and 375 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 22.5 g of sodium benzoic acid-3,5-disulfonate, 7.5 g of dicyclohexylcarbodiimide and 3.75 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 35 ° C. for 8 h, concentrated under reduced pressure, separated by column chromatography, and dried to obtain a multi-arm alkenyl betaine type cross-linking agent.
[0039] (3) Under nitrogen atmosphere, 1.2 g of succinic anhydride and 400 mL of acetone were added to the reaction flask. After stirring evenly, 20 g of polyethylene glycol monomethyl ether was added and stirred at 35 °C for 16 h. 1.6 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1 g of N-hydroxysuccinimide and 3 g of chitosan were added and stirred for 12 h. After dialysis and drying, polyethylene glycol monomethyl ether modified chitosan was obtained.
[0040] (4) Under a nitrogen atmosphere, 100 g acrylamide, 5 g acrylic acid, 1.5 g organic dispersant, 0.9 g polyethylene glycol monomethyl ether modified chitosan and 0.1 g multi-arm ene betaine type cross-linking agent were stirred uniformly at room temperature, then added to a 0.1 g / mL sodium citrate trisodium aqueous solution, mixed uniformly, degassed with nitrogen for 30 min, added with 0.03 g ammonium persulfate, stirred for 40 min, transferred to a mold, polymerized at 80 ° C for 3 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0041] Example 3
[0042] (1) Under nitrogen atmosphere, 20 g of triallylamine and 300 mL of ethanol were added to a reaction flask. After stirring, 10 g of 1,3-dibromo-2-propanol and 17 g of triethylamine were added. The mixture was reacted at 60 °C for 48 h, concentrated under reduced pressure, and dried to obtain hexaallyl quaternary ammonium salt propanol.
[0043] (2) Under nitrogen atmosphere, 18 g of hexaallyl quaternary ammonium salt propanol and 360 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 18.9 g of sodium benzoic acid-3,5-disulfonate, 8.1 g of dicyclohexylcarbodiimide and 5.4 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 20° C. for 16 h, concentrated under reduced pressure, separated by column chromatography, and dried to obtain a multi-arm alkenyl betaine type cross-linking agent.
[0044] (3) Under nitrogen atmosphere, 1.5 g of succinic anhydride and 375 mL of acetone were added to the reaction flask. After stirring evenly, 15 g of polyethylene glycol monomethyl ether was added and stirred at 20°C for 32 h. 1.8 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 1.35 g of N-hydroxysuccinimide and 3.75 g of chitosan were added and stirring was continued for 24 h. After dialysis and drying, polyethylene glycol monomethyl ether modified chitosan was obtained.
[0045] (4) Under a nitrogen atmosphere, 100 g of acrylamide, 10 g of acrylic acid, 3 g of an organic dispersant, 0.9 g of polyethylene glycol monomethyl ether-modified chitosan and 0.15 g of a multi-arm olefin betaine-type crosslinking agent were stirred uniformly at room temperature, then added to a 0.2 g / mL sodium citrate aqueous solution, mixed uniformly, degassed with nitrogen for 15 min, 0.06 g of ammonium persulfate was added, stirring was continued for 20 min, transferred to a mold, polymerized at 60 ° C for 8 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0046] Example 4
[0047] (1) Under nitrogen atmosphere, 65 g of triallylamine and 900 mL of ethanol were added to a reaction flask. After stirring, 27.3 g of 1,3-dibromo-2-propanol and 53.3 g of triethylamine were added. The mixture was reacted at 75 °C for 32 h, concentrated under reduced pressure, and dried to obtain hexaallyl quaternary ammonium salt propanol.
[0048] (2) Under a nitrogen atmosphere, 50 g of hexaallyl quaternary ammonium salt propanol and 800 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 51 g of sodium benzoic acid-3,5-disulfonate, 18 g of dicyclohexylcarbodiimide and 12 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 30° C. for 12 h, concentrated under reduced pressure, separated by column chromatography, and dried to obtain a multi-arm alkenyl betaine type cross-linking agent.
[0049] (3) Under nitrogen atmosphere, 3.2 g of succinic anhydride and 920 mL of acetone were added to the reaction flask. After stirring evenly, 40 g of polyethylene glycol monomethyl ether was added and stirred at 35 °C for 24 h. 4.4 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 3 g of N-hydroxysuccinimide and 7.2 g of chitosan were added and stirred for another 24 h. After dialysis and drying, polyethylene glycol monomethyl ether-modified chitosan was obtained.
[0050] (4) Under a nitrogen atmosphere, 100 g of acrylamide, 9 g of acrylic acid, 2 g of an organic dispersant, 0.6 g of polyethylene glycol monomethyl ether-modified chitosan and 0.25 g of a multi-arm olefin betaine-type crosslinking agent were stirred uniformly at room temperature, then added to a 0.15 g / mL sodium citrate trisodium aqueous solution, mixed uniformly, degassed with nitrogen for 25 min, added with 0.04 g of ammonium persulfate, stirred for 30 min, transferred to a mold, polymerized at 75 °C for 6 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0051] Example 5
[0052] (1) Under nitrogen atmosphere, 15 g of triallylamine and 200 mL of ethanol were added to a reaction flask. After stirring, 7.5 g of 1,3-dibromo-2-propanol and 11.7 g of triethylamine were added. The mixture was reacted at 65 °C for 36 h, concentrated under reduced pressure, and dried to obtain hexaallyl quaternary ammonium salt propanol.
[0053] (2) Under nitrogen atmosphere, 12 g of hexaallyl quaternary ammonium salt propanol and 220 mL of dichloromethane were added to a reaction flask, and after stirring evenly, 11.4 g of sodium benzoic acid-3,5-disulfonate, 4.2 g of dicyclohexylcarbodiimide and 3 g of 4-dimethylaminopyridine were added, and the mixture was reacted at 30° C. for 15 h, concentrated under reduced pressure, separated by column chromatography, and dried to obtain a multi-arm alkenyl betaine type cross-linking agent.
[0054] (3) Under nitrogen atmosphere, 0.8 g of succinic anhydride and 240 mL of acetone were added to the reaction flask. After stirring evenly, 10 g of polyethylene glycol monomethyl ether was added and stirred at 30 °C for 24 h. 1.1 g of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 0.7 g of N-hydroxysuccinimide and 2.5 g of chitosan were added and stirred for another 24 h. After dialysis and drying, polyethylene glycol monomethyl ether-modified chitosan was obtained.
[0055] (4) Under a nitrogen atmosphere, 100 g of acrylamide, 9 g of acrylic acid, 3 g of an organic dispersant, 7 g of polyethylene glycol monomethyl ether-modified chitosan and 0.25 g of a multi-arm ene betaine-type crosslinking agent were stirred uniformly at room temperature, then added to a 0.12 g / mL sodium citrate trisodium aqueous solution, mixed uniformly, degassed with nitrogen for 25 min, added with 0.05 g of ammonium persulfate, stirred for 35 min, transferred to a mold, polymerized at 80 ° C for 8 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0056] Comparative Example 1
[0057] Under a nitrogen atmosphere, 100 g of acrylamide, 8 g of acrylic acid, 2.5 g of an organic dispersant, 0.8 g of polyethylene glycol monomethyl ether modified chitosan (prepared in Example 1) and 0.05 g of hexaallyl quaternary ammonium salt propanol (prepared in Example 1) were stirred evenly at room temperature, and then added to a trisodium citrate aqueous solution with a mass concentration of 0.15 g / mL. After mixing evenly, the mixture was degassed with nitrogen for 25 min, 0.05 g of ammonium persulfate was added, stirring was continued for 30 min, and the mixture was transferred to a mold, polymerized at 70 ° C for 5 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0058] Comparative Example 2
[0059] Under a nitrogen atmosphere, 100 g acrylamide, 8 g acrylic acid, 2.5 g organic dispersant, 0.8 g polyethylene glycol monomethyl ether modified chitosan (prepared in Example 1) and 0.05 g triallylamine were stirred at room temperature, then added to a 0.15 g / mL trisodium citrate aqueous solution, mixed evenly, degassed with nitrogen for 25 min, 0.05 g ammonium persulfate was added, stirring was continued for 30 min, transferred to a mold, polymerized at 70 ° C for 5 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0060] Comparative Example 3
[0061] Under a nitrogen atmosphere, 100 g acrylamide, 8 g acrylic acid, 2.5 g organic dispersant and 0.8 g chitosan were stirred evenly at room temperature, then added to a trisodium citrate aqueous solution with a mass concentration of 0.15 g / mL. After mixing evenly, the mixture was degassed with nitrogen for 25 min, 0.05 g ammonium persulfate was added, stirring was continued for 30 min, the mixture was transferred to a mold, polymerized at 70 °C for 5 h, and cooled to room temperature to obtain a conductive hydrogel matrix.
[0062] Mechanical properties test: The conductive hydrogel matrix was subjected to a tensile properties test using a universal material testing machine. A 200N sensor was used during the test and the specimen was cut into a dumbbell shape with a specification of 35 mm × 2 mm × 1.5 mm. The original gauge length (i.e., effective tensile length) was set to 15 mm and the tensile rate was 80 mm / min.
[0063] Table 1 Mechanical properties test
[0064]
[0065]
[0066] It can be seen from the test results in the above table that with the increase of the content of the multi-arm alkenyl betaine type cross-linking agent, the mechanical properties of the conductive hydrogel matrix are gradually enhanced. The tensile strength in Example 4 reaches 0.51 MPa, and the tensile strain reaches 391.40%, which has good flexibility; this is because the multi-arm alkenyl betaine type cross-linking agent contains six alkenyl structures, which can be polymerized with acrylamide and the like to form a dense three-dimensional cross-linked network structure. When an external force is used for stretching, more energy is required to move the molecular segments; at the same time, chitosan has good water dispersibility after being modified with polyethylene glycol monomethyl ether, and forms physical crosslinks with the hydrogel network through strong hydrogen bonds. At the same time, the physical entanglement of the internal network of the organic hydrogel itself and the strong hydrogen bonds of chitosan synergistically form a strong physical crosslinking interaction, and by combining with the original chemical crosslinking, a compact organic hydrogel is formed together, and excellent mechanical properties are given to it. The compact network structure is conducive to avoiding stress concentration and crack diffusion, and plays a vital role in the toughening of the conductive hydrogel matrix.
[0067] Since the hydrogel uses glycerol salt solution, low concentration potassium chloride solution and non-toxic glycerol to the human body, the organic hydrogel can ensure good biocompatibility on the surface of human skin. In addition, glycerol and acrylamide, acrylic acid, etc. contain strong hydrogen bonding, which can also ensure that the conductive hydrogel matrix has good adhesion on the skin surface.
[0068] Conductive performance test: The conductive hydrogel matrix was cut into small discs with a thickness of 1.5 mm and a diameter of 15.8 mm. The electrochemical workstation was used to perform the AC impedance method at 0.1-1×10 5 The resistance of the conductive hydrogel matrix was measured in the Hz frequency range, the voltage of the electrochemical workstation was set to 5mV, and the conductivity = L / RS, where L is the distance between the two electrodes (the thickness of the conductive hydrogel matrix), cm; R is the resistance of the conductive hydrogel matrix, Ω; S is the effective cross-sectional area of the conductive hydrogel matrix, cm 2 .
[0069] Table 2 Conductivity test
[0070] Conductivity (S / m) Example 1 3.68 Example 2 4.21 Example 3 6.35 Example 4 8.21 Example 5 10.24 Comparative Example 1 2.53 Comparative Example 2 1.03 Comparative Example 3 0.68
[0071] It can be seen from the test results in the above table that with the increase of the content of the multi-arm alkenyl betaine type cross-linking agent, the conductivity of the conductive hydrogel matrix is gradually enhanced, wherein the conductivity of Example 5 reaches 10.24S / m. This is because the multi-arm alkenyl betaine type cross-linking agent contains quaternary ammonium salt and sodium sulfonate zwitterions, wherein the dipole-dipole interaction is conducive to ion migration, and can release the maximum concentration of freely moving ions. At the same time, the modified chitosan is evenly dispersed in the matrix, and the network structure formed provides a better conductive channel for ion migration, further improving the ion migration rate and conductivity, thereby ensuring that the hydrogel has excellent conductivity, which is conducive to sensitive signal transmission.
[0072] Bonding strength test: The tensile shear strength test was carried out on a universal material testing machine with a tensile rate of 100 mm / min to reflect the bonding performance of the hydrogel to the substrate. The sample had a double overlap structure with an overlap area of 25 mm×12.5 mm. A longitudinal tensile shear force was applied to the overlap surface of the sample with a loading rate of 5 mm / min. The maximum load of the shear failure of the sample divided by the overlap area was the bonding interface shear strength of the conductive hydrogel matrix to the test substrate.
[0073] Table 3 Adhesion performance test
[0074]
[0075] It can be seen from the test results in the above table that the conductive hydrogel matrix can be tightly bonded to substrates such as rubber and tinplate with high bonding strength, which overcomes the problem of poor adhesion between the existing hydrogel matrix and tissues, and further enables the flexible strain sensor to be seamlessly connected to the human body.
[0076] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a conductive hydrogel matrix, characterized in that: The preparation method comprises the following steps: Step (1), under a nitrogen atmosphere, add succinic anhydride and acetone to a reaction flask, stir evenly, add polyethylene glycol monomethyl ether, stir at 20-35° C. for 16-32 hours, add 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and chitosan, continue stirring for 12-24 hours, and after dialysis and drying, obtain polyethylene glycol monomethyl ether modified chitosan; Step (2), under nitrogen atmosphere, acrylamide, acrylic acid, organic dispersant, polyethylene glycol monomethyl ether modified chitosan and a structural formula The multi-arm alkenyl betaine type cross-linking agent is stirred evenly at room temperature, and then added to a trisodium citrate aqueous solution with a mass concentration of 0.1-0.2 g / mL. After mixing evenly, it is degassed with nitrogen for 15-30 minutes, ammonium persulfate is added, and stirring is continued for 20-40 minutes. The mixture is transferred to a mold, polymerized at 60-80°C for 3-8 hours, and cooled to room temperature to obtain a conductive hydrogel matrix.
2. The method for preparing a conductive hydrogel matrix according to claim 1, characterized in that: In the step (1), the ratio of succinic anhydride, polyethylene glycol monomethyl ether, 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, N-hydroxysuccinimide and chitosan is (6-10) g:100 g:(8-12) g:(5-9) g:(15-25) g.
3. The method for preparing a conductive hydrogel matrix according to claim 1, characterized in that: In the step (2), the organic dispersant is potassium chloride and glycerol mixed in a mass ratio of 1:
1.
4. The method for preparing a conductive hydrogel matrix according to claim 1, characterized in that: In the step (2), the ratio of acrylamide, acrylic acid, organic dispersant, polyethylene glycol monomethyl ether modified chitosan, multi-arm alkenyl betaine type cross-linking agent, and ammonium persulfate is 100g: (5-10)g: (1.5-3)g: (0.5-0.9)g: (0.05-0.25)g: (0.03-0.06)g.
5. The method for preparing a conductive hydrogel matrix according to claim 1, characterized in that: The preparation method of the multi-arm alkenyl betaine type cross-linking agent in step (2) comprises the following steps: Step S1, under a nitrogen atmosphere, add triallylamine and ethanol to a reaction flask, stir evenly, then add 1,3-dibromo-2-propanol and triethylamine, stir to react, after the reaction is completed, concentrate under reduced pressure, and dry to obtain hexaallyl quaternary ammonium salt propanol; Step S2, under a nitrogen atmosphere, add hexaallyl quaternary ammonium salt propanol and dichloromethane to a reaction flask, stir evenly, add sodium benzoic acid-3,5-disulfonate, dicyclohexylcarbodiimide and 4-dimethylaminopyridine, react at 20-35° C. for 8-16 hours, concentrate under reduced pressure, separate by column chromatography, and dry to obtain a multi-arm alkenyl betaine type cross-linking agent.
6. The method for preparing a conductive hydrogel matrix according to claim 5, characterized in that: In the step S1, the ratio of triallylamine, 1,3-dibromo-2-propanol and triethylamine is 100 g:(35-50) g:(75-85) g.
7. The method for preparing a conductive hydrogel matrix according to claim 5, characterized in that: In step S1, the reaction temperature is 60-80° C. and the reaction time is 24-48 hours.
8. The method for preparing a conductive hydrogel matrix according to claim 5, characterized in that: In the step S2, the ratio of hexaallyl quaternary ammonium salt propanol, sodium benzoic acid-3,5-disulfonate, dicyclohexylcarbodiimide, and 4-dimethylaminopyridine is 100 g: (90-105) g: (30-45) g: (15-30) g.
9. A flexible strain sensor, characterized in that: The conductive hydrogel matrix obtained by the preparation method according to any one of claims 1 to 8 is installed with electrodes to form a flexible strain sensor.
10. Application of the flexible strain sensor according to claim 9 in the preparation of electronic skin, smart clothing, flexible smart robots, foldable displays, and tensile strain detection equipment.
Citation Information
Cited By
Antistatic protective film
CN120757943A